The comparison of nuclear ubiquitous casein and cyclin-dependent kinases substrate (NUCKS) with Ki67 proliferation marker expression in common skin tumors - Zduniak, Krzysztof; Agrawal, Siddarth; Symonowicz, Krzysztof; Jurczyszyn, Kamil; Ziółkowski, Piotr (Polish Journal of Pathology, 2014)
Nuclear ubiquitous casein and cyclin-dependent kinases substrate (NUCKS) is a chromosomal protein of unknown function. Its amino acid composition and structure of its DNA binding domain resemble those of high mobility group A (HMGA) proteins which are associated with various malignancies. Since changes in expression of HMGA are considered as a marker of tumor progression, it is possible that similar changes in expression of NUCKS could be a useful tool in diagnosis of malignant skin tumors. To investigate this assumption we used specific antibodies against NUCKS for immunohistochemistry of squamous (SCC) and basal cell carcinoma (BCC) as well as keratoacanthoma (KA). We found high expression of NUCKS in nuclei of SCC and BCC cells which exceeded expression of the well-known proliferation marker Ki67. Expression of NUCKS in benign KA was much below that of malignant tumors. With the present study and based on our previous experience we would like to suggest the NUCKS protein as a novel proliferation marker for immunohistochemical evaluation of formalin-fixed and paraffin-embedded skin tumor specimens. We would like to emphasize that NUCKS abundance in malignant skin tumors is higher than that of the well-known proliferation marker Ki67, thus allowing more precise assessment of tumor proliferation potential.